Diabetic kidney disease progression is associated with decreased lower-limb muscle mass and increased visceral fat area in T2DM patients - Lin, Xiaopu; Chen, Zhenguo; Huang, Haishan; Zhong, Jingyi; Xu, Lingling (Frontiers in Endocrinology, 2022)
Aim This study aimed to explore the relationship between lower-limb muscle mass/visceral fat area and diabetic kidney disease (DKD) progression in patients with type 2 diabetes mellitus (T2DM). Methods A total of 879 participants with T2DM were divided into 4 groups according to the prognosis of CKD classification from Kidney Disease: Improving Global Outcomes (KDIGO). Rectus femoris cross-sectional area (RFCSA) was measured through ultrasound, and visceral fat area (VFA) was evaluated with bioelectric impedance analysis (BIA). Results T2DM patients with high to very high prognostic risk of DKD showed a reduced RFCSA (male P < 0.001; female P < 0.05), and an enlarged VFA (male P < 0.05; female P < 0.05). The prognostic risk of DKD was negatively correlated with RFCSA (P < 0.05), but positively correlated with VFA (P < 0.05). Receiver-operating characteristic analysis revealed that the cutoff points of T2DM duration combined with RFCSA and VFA were as follows: (male: 7 years, 6.60 cm2, and 111 cm2; AUC = 0.82; 95% CI: 0.78–0.88; sensitivity, 78.0%; specificity, 68.6%, P < 0.001) (female: 9 years, 5.05 cm2, and 91 cm2; AUC = 0.73; 95% CI: 0.66–0.81; sensitivity, 73.9%; specificity, 63.3%, P < 0.001). Conclusion A significant association was demonstrated between reduced RFCSA/increased VFA and high- to very high-prognostic risk of DKD. T2DM duration, RFCSA, and VFA may be valuable markers of DKD progression in patients with T2DM. Clinical trial registration http://www.chictr.org.cn, identifier ChiCTR2100042214